The Persuasive Language Used in Advertisements in Magazine - Siti Yuliah; Januar Fitriyandi; Muhammad Yahya (Jurnal Bahasa Inggris Terapan, 2021)
This paper presents the results of the study on analyzing the persuasive language used in advertisements in magazines. The aim of this study is to identify the types of persuasive language used in advertisements in Forbes magazine and to analyze the dominant types of persuasive language found in the advertisements. Therefore, the qualitative data were collected from a recognized magazine entitled “Forbes”. The data were analyzed based on the types of persuasive language found by Kannan & Tyagi (2013). The results show that there are 10 types of persuasive languages used in the advertisements in Forbes magazine: long noun phrases, short sentences, avoidance of negative, use of imperatives, weasel words and repetition, hyperbole, simple and colloquial language, alliteration, and syntactic parallelism. Among the 10 persuasive language types, the most dominant one is long noun phrases. The implication of the study may be used to EFL learning and teaching and translation persuasive languages.